PENGARUH INFLASI, KINERJA KEUANGAN DAN KURS TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PERTAMBANGAN PASAR MODAL INDONESIA - Ahmad Nazri; Ustadus Sholihin; Helmi Agus Salim; Ardi Halim (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The purpose of this study is to find out whether inflation, financial performance and exchange rates affect stock prices in mining sector companies registered in the Indonesian Capital Market, the oil and gas sub-sector. The population in this study is a report on inflation, CR, ROA, exchange rates and stock prices for the period 2013-2017, the population of this study is 2 companies and there are data samples of 40 monthly 3-period observations. The analysis technique uses the classic assumption test, multiple regression test, t test, F test and determinant coefficient test. Partially the inflation results do not have a partial effect on stock prices, cr has a partial effect on stock prices, roa has no partial effect on stock prices, exchange rates does not have a partial effect on stock prices. Then inflation, cr, roa and exchange rates have a simultaneous effect on stock prices. Furthermore, the R2 results of this study amounted to 0.357 or 35.7% which could influence stock prices.